The Influence of Medial Comminution in the Treatment Choice of Radial Head Fracture - Touloupakis, G (Malays Orthop J, 2020)
INTRODUCTION: The aim of our retrospective study was to investigate the role of the medial side involvement in the treatment choice of radial head fractures. MATERIALS AND METHODS: We searched the databases of our institutions for the surgical procedures diagnosed as "fracture of the radial head" and for the procedures related to "prosthesis of the radial head" and "osteosynthesis of the radial head" in the period from May 2014 to October 2017. The fractures were first classified according to the Mason classification . We then allocated the patients into three study groups according to the site of the fracture, either the medial or lateral side of the radial head : Group A, with an isolated lateral fracture of the radius head; Group B1, with a medial fracture of the radius head with two medial fragments; and Group B2, with a medial fracture of the radius head with multiple medial fragments. We performed a multivariate analysis to identify statistically significant correlation between the pre-operative classifications of Mason and our study, the type of surgical procedure, and the clinical outcome. RESULTS: Mayo Elbow Performance (MEP) scores determined at the final follow-up of the study (mean 16.6 months, range 12-26 months) was excellent in 17 patients (4 in Group A, 6 in Group B1 and 7 in Group B2), and good in 12 patients (3 in Group A, 7 in Group B1, and 2 in Group B2). One patient showed a poor result in MEP score probably because of an infection and implant removal. CONCLUSION: Regarding medial fractures of the radial head, our study showed satisfactory results with a radial head prosthesis for comminuted or multifragmentary radial head fractures. For surgeons with advanced elbow fracture expertise, osteosynthesis could be attempted in a fracture pattern that involved only two medial fragments.